Semi-Markov reward models for disability insurance - Stenberg, F.; Manca, R.; Silvestrov, D. (Інститут математики НАН України, 2006)
A semi-Markov model for disability insurance is described. Statistical evidences of relevance semi-Markov setting are given. High order semi-Markov backward reward models are invented. Applications of these
models to proﬁt-risk analysis of disability insurance contracts are considered.